MORPHOLOGICAL AND GENOTYPIC FEATURES OF THE POPULATIONS OF FLEAS OF THE GENUS XENOPSYLLA GLINKIEWICZ, 1907 (SIPHONAPTERA, PULICIDAE) FROM THE AUTONOMOUS FOCI OF THE CENTRAL ASIAN NATURAL DESERT PLAGUE FOCUS - Zhaure Sayakova; Alexandr Shevtsov; Bakyt Atshabar; Altyn Rysbekova; Andrey Kuznetsov; Veronika Sadovskaya; Erlan M. Ramankulov; Sabyr T. Nurtazhin; Aigul Abdirasilova; Aydin Eszhanov (Scientific Journal of Pedagogy and Economics, 2021)
The paper presents the results of the study of some morphological and genotypic features of fleas of the genus Xenopsylla: X. gerbilli minax, X. skrjabini, X. hirtipes - the main vectors in the Central Asian natural desert plague focus. In order to identify population characteristics, for the first time we attempted both morphological analysis using the ImageJ computer program and subsequent data processing in a free statistical environment R version 4.0.0 with R Studio graphic shell, as well as genetic analysis of a fragment of a nucleotide sequence of the COII gene of fleas sampled in Pre-Ustyurt, Betpakdala and Pre-Pre-Balkhash autonomous plague foci. As a result of the study of morphometric indices of the main plague vectors in Kazakhstan, independent populations of three species of fleas of the genus Xenopsylla have been identified: the Betpakdala and Pre-Pre-Balkhash populations of X. gerbilli minax and X. hirtipes, as well as the Pre-Pre-Balkhash, Betpakdala and Pre-Usturt populations of X. skrjabini fleas.